Sub-recente marine ostracoda (pontocyprididae and bairdiidae) from the southern continental shelf. - Ramos, Maria Inês Feijó (2004)
This work is part of a long-term project that attempts to describe the Ostracoda present in the southem Brazilian shelf between Rio de Janeiro and Rio Grande do Sul state (almost 2,050 km in length), and to assess the zoogeographical significance of a total 102 benthic species. In this paper the families Pontocyprididae and Bairdiidae have been identified with the description of five new taxa: Argilloecia inflata, A. subacuta, Pontocypris? punctatus, Baiirdoppilata sud brasiliensis, and Neonesidea? rotunda. Argiloecia parameridionalis Whatley et ali., is here recorded farther north than previous records.